Influence of interface sawtooth angle on the shear behavior of cement mortar coal composite structure - Xianxia Wang; Xudong Shi; Jinwen Bai; Hongchao Zhao; Yantong Zhao (Scientific Reports)
Abstract The influence of interface morphology is of great importance on the shear behavior of the cement mortar-coal composite structure (CCCS) widely distributed in underground mines. In the present research, both the macroscopic- and microscopic failure characteristics of the CCCS with variable interface sawtooth angles (i.e., 0°, 15°, 30°, 45°, 60°, 75°) were experimentally and numerically investigated. The results showed that both the shear strength and displacement of tested specimen increased with the increase of the interface sawtooth angle. The peak stress is 5.42 MPa at a sawtooth angle of 75°, which is 1.369 times that of the specimen with a sawtooth angle of 0°. The typical failure modes of tested specimens can be classified into three categories: the climbing failure, the cutting failure, and the sliding failure. As the interface sawtooth angle increases, the climbing damage changes to cutting damage. The increase in sawtooth angle prolonged the duration of stress concentration in the sample. And the sawtooth angle changed the stress distribution of the sample, resulting in a different final failure pattern as well as a different residual strength. This study is expected to provide theoretical guidance for the prevention and control of shear instability in CCCS.